2011
DOI: 10.1097/coc.0b013e3181d26b1a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of kV Cone-Beam CT Performance for Prostate IGRT

Abstract: CBCT with soft-tissue-based automatic corrections is not an accurate alignment compared with manual alignment to fiducial markers for prostate IGRT. We have concluded that a daily manual alignment to fiducials is one of the most reliable methods to maintain accuracy in prostate IGRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In select patients, daily manual alignment to fiducials is one of the most reliable methods of maintaining accuracy in prostate IGRT, more so than CBCT with soft tissue–based automatic corrections. 30 Implanting fiducials through either a transperineal or transrectal approach is an invasive procedure but has a low rate of complications. 31 Although seeds may theoretically migrate, this is generally not a significant problem because fiducial markers have been shown to be stable within the prostate, 32 even when implanted on the same day as the simulation.…”
Section: Methods For Image Guided Radiation Therapymentioning
confidence: 99%
“…In select patients, daily manual alignment to fiducials is one of the most reliable methods of maintaining accuracy in prostate IGRT, more so than CBCT with soft tissue–based automatic corrections. 30 Implanting fiducials through either a transperineal or transrectal approach is an invasive procedure but has a low rate of complications. 31 Although seeds may theoretically migrate, this is generally not a significant problem because fiducial markers have been shown to be stable within the prostate, 32 even when implanted on the same day as the simulation.…”
Section: Methods For Image Guided Radiation Therapymentioning
confidence: 99%
“…Image-guided radiation therapy (IGRT) technology has been widely adopted to provide anatomic information with the patient in the treatment position. With image guidance (typically X-ray imaging such as kilovolt (kV), megavolt (MV), and CBCT), the patient positions in the daily images are registered to the planning images based on either bony landmarks or soft tissues [1618, 21, 22]. Furthermore, fiducial markers for prostate IGRT have been in use since the 1990s and O’Neill et al reviewed the evidence for the use of fiducial markers in clinical practice [23].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IGRT based on CBCT-ST has become the main stream method of radiotherapy for prostate cancer, and rigorous and accurate setting of the PTV margin is also indispensable for this procedure, as well as with other image-guided techniques. In kV-CBCT, reports on inter- and intra-observer variabilities for on-line matching registration due to ambiguity and inadequacy of its image quality have been reported in various forms [ 26 , 33 35 ]. Lutgendorf-Caucig et al confirmed that, since delineation using kV-CBCT has larger inter-observer variability than normal CT and MRI images, planning with appropriate safety margins by taking this effect into consideration is necessary for CBCT-based adaptive radiotherapy (ART) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%